BRIDGING THE BARRIERS IN BRITISH CULTURE - Hallouch, Nadjouia (PEOPLE: International Journal of Social Sciences, 2019)
There is a general observation among officials that the conflict between cultures has been dramatically increasing. This can be related to a whole set of reasons including: cultural unawareness, prejudice, the ignorance of differences in values, norms and beliefs and the media. The module of British culture is taught at the Departments of English in the Algerian universities from the first year. Many students think that in the course of British culture, the teacher is the only performer whose duty is to give them information about the target culture. Teaching British culture does not require from the teacher transmitting only information but developing positive attitudes, skills and awareness of values of this culture (Byram, Gribkova, & Starkey, 2002). The questions which are raised here are: are we as teachers of British culture preparing our students for a successful intercultural communication? Are we helping our students to develop their cultural awareness? This research paper was carried out through a questionnaire applied to second year students in British culture in particular to assess their cultural awareness. It focusses on the role of the teacher in helping students bridging the barriers and enabling them to interact successfully with people from other cultures.